Design and Implementation of Slipper Loan and Safety Systems Using Ultrasonic Sensors and Internet of Things Based RFID Sensors - Dimas Dwi Priyono; Aulia Desy Nur Utomo; Yoso Adi Setyoko (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2023)
The comfort of the mosque is a top priority, so visitors feel comfortable when praying. For example, borrowing sarongs and safety sandals still uses a manual system. Borrowing mosque sarongs, for the most part, cannot known how many of them are available, and the safety of the sandals makes it familiar for visitors to exchange sandals and even lose their sandals. So digitization is needed as displayed on the LCD screen or website in designing this system, using the prototype method to detect system errors more quickly. In addition, this system was built using the PHP language with a more flexible website appearance and testing using a black box. So that by making this system, mosque visitors become more comfortable in carrying out worship.